KINERJA KEUANGAN DAN DAMPAKNYA TERHADAP ZAKAT BANK SYARIAH: ANALISIS PADA BUS TERDAFTAR DI OJK (2015–2019) - Sri Wulan Dari (Journal Tafkirul Iqtishodiyyah, 2025)
The rapid development of Islamic banking in Indonesia positions zakat as a key instrument of accountability and Sharia compliance. However, prior studies examining the relationship between financial performance and zakat show inconsistent findings, particularly concerning profitability indicators such as Return on Assets (ROA) and Return on Equity (ROE). This study aims to analyze the effect of ROA and ROE on zakat payments of Islamic Commercial Banks (BUS) registered with the Financial Services Authority (OJK) during 2015–2019. Using a causal quantitative approach, this research employs secondary data obtained from the annual reports of three state-owned Islamic banks BNI Syariah, Bank Syariah Mandiri, and BRI Syariah selected through purposive sampling. Data were analyzed using classical assumption tests and multiple linear regression to examine both partial and simultaneous effects. The results indicate that ROA has a negative and significant effect on zakat, whereas ROE has a positive and significant effect. Simultaneously, ROA and ROE significantly influence zakat, explaining 57.1% of the variation. These findings confirm that profitability is a key determinant of corporate zakat obligations, implying that better management of assets and equity leads to greater zakat contributions. This study enriches the empirical literature on zakat accountability in Islamic banking, although its generalizability is limited by sample size and variable scope. Future research is suggested to incorporate additional variables such as bank size, operational efficiency, and Sharia governance and expand the range of samples for more comprehensive insights.